Feasibility study for the elaboration of shrimp meat nuggets (litopenaeus vannamei) enriched with quinoa (chenopodium quinoa) as a nutritional alternative for the population of guayaquilaña. - Ochoa Palma, Marcia Idilma; Muñoz Meza, Simón Alejandro (Ingeniería Química y Desarrollo, 2023)
In the following investigation work a study is carried out for the elaboration of shrimp nuggets (Litopenaeus vannamei) enriched with quinoa (Chenopodium Quinoa) from shrimp meat as a real gastronomic alternative for Guayaquil city and in turn expand the food offer in the country, Shrimp is a symbolic product for the country, from which delicious Ecuadorian dishes are obtained are typical in the cities and towns of the country. The data and history of shrimp activity are investigated and observed, beginning with the generalities of shrimp, its production at the national level, the life cycle of shrimp and everything that involves shrimp and quinoa production. INIAP Thunkahuán. At the same time, the research method to be used in the present work is analyzed, seeking to find the ideal method to find the way to elaborate the nugget and, at the same time, to observe which is the nugget that the Guayaquil population would like to acquire and consume.The main idea to elaborate the nugget is to give to Guayaquil citizens a nutritious alternative based on this seafood in order to give the Guayaquil population a healthy option. With which in turn it is also sought to strengthen the economy and consumption of these indigenous products, experiments are carried out to observe the preference of the product with which the liking of the judges was observed, demonstrating that there is a technical and economic possibility for the elaboration of the shrimp nugget enriched with quinoa.